Insulin-Sensitizing Properties of Decoctions from Leaves, Stems, and Roots of Cucumis prophetarum L. - Zewdie Mekonnen; Giuseppe Petito; Getasew Shitaye; Gianluca D’Abrosca; Belete Adefris Legesse; Sisay Addisu; Maurizio Ragni; Antonia Lanni; Roberto Fattorusso; Carla Isernia; Lara Comune; Simona Piccolella; et al. (Molecules)
Type 2 diabetes mellitus (T2DM) is a chronic disease characterized by insulin resistance and impaired beta-cell secretory function. Since existing treatments often present side effects based on different mechanisms, alternative therapeutic options are needed. In this scenario, the present study first evaluates the cytotoxicity of decoctions from the leaves, stems, and roots of Cucumis prophetarum L. on HepG2 and L6C5 cells. The extracts were chemically investigated by UV–Vis and ATR-FTIR spectroscopic techniques and by ultra high-performance chromatographic techniques, coupled with high-resolution mass spectrometry. Briefly, decoctions from the leaves and stems were mainly composed of apigenin C-glycosides, while the root decoction was rich in raffinose and cucumegastigmane II. To evaluate the insulin-sensitizing properties of the extracts in insulin-resistant L6 myoblasts, an evaluation by Western blot analysis of the proteins in the insulin signaling pathway was then performed. Particularly, key proteins of insulin signaling were investigated, i.e., insulin receptor substrate (IRS-1), protein kinase B (PKB/AKT), and glycogen synthase kinase-3 (GSK-3β), which have gained considerable attention from scientists for the treatment of diabetes. Under all conditions tested, the three decoctions showed low cytotoxicity. The stem and root decoction (300 μg/mL) resulted in a significant increase in the levels of p-IRS-1 (Tyr612), GSK3β (Ser9), and p-AMPK (Thr172) compared to those of the palmitic acid-treated group, and the leaf decoction resulted an increase in the level of p-IRS-1 (Tyr612) and p-AMPK (Thr172) and a decrease in p-GSK3β (Ser9) compared to the levels for the palmitic acid-treated group. The root decoction also reduced the level of p-mToR (Ser2448). Overall, the acquired data demonstrate the effect of reducing insulin resistance induced by the investigated decoctions, opening new scenarios for the evaluation of these effects aimed at counteracting diabetes and related diseases in animal models.